Preparation method and application of nitrogen-doped graphite carbon coated bismuth zinc ferrite negative electrode coating material

By using nitrogen-doped graphite carbon to coat bismuth zinc ferrate negative electrode coating material in aqueous zinc ion batteries, the problems of zinc dendrites growth and hydrogen evolution reaction are solved, and the stability and service life of the battery are significantly improved.

CN119852297AActive Publication Date: 2025-04-18DALIAN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411950015.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-18
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Existing aqueous zinc ion batteries face problems such as zinc dendrites growth, zinc negative electrode surface corrosion and hydrogen evolution reaction, resulting in low Coulomb efficiency, poor reversibility and fast capacity attenuation.

Method used

The nitrogen-doped graphite carbon coated bismuth zinc ferrate negative electrode coating material is used as the negative electrode interface coating of the aqueous zinc ion battery. This material is prepared by thermal synthesis method and coated on the surface of metal zinc foil to provide rich oxygen vacancies and nitrogen sites, and inhibit zinc dendrites' growth and hydrogen evolution reaction.

Benefits of technology

Effectively inhibit the growth of zinc dendrites, improve the stability and service life of the battery, and significantly improve the cycle stability and capacity retention of aqueous zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005214639060000011
    Figure HDA0005214639060000011
  • Figure HDA0005214639060000012
    Figure HDA0005214639060000012
  • Figure HDA0005214639060000013
    Figure HDA0005214639060000013
Patent Text Reader

Abstract

The invention belongs to the technical field of aqueous zinc ion batteries, and discloses a preparation method and application of a nitrogen-doped graphite carbon coated bismuth zinc ferrite negative electrode coating material. A nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material is prepared, and the material is used for preparing an aqueous zinc ion battery negative electrode material. According to the aqueous zinc ion battery negative electrode coating material, the surface of a metal zinc foil is coated with nitrogen-doped graphite carbon-coated bismuth ferrite, and abundant active sites can be provided, so that zinc ions can be relatively uniformly deposited, and the growth of zinc dendrites is inhibited; the material has excellent mechanical strength and chemical stability, so that the corrosion of electrolyte to the negative electrode is effectively inhibited; the impedance of a symmetrical battery assembled by the material is obviously reduced compared with that of pure zinc, the half-battery cycle efficiency stability is obviously improved, and the service life of an aqueous zinc ion battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aqueous zinc ion batteries, and the present invention relates to a preparation method and application of a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material, and specifically to a preparation method of an aqueous zinc ion battery negative electrode coating material. Background Art

[0002] With the rapid development of wearable devices and electric vehicles, the new energy storage industry has developed rapidly. At present, lithium batteries have been fully commercialized. However, due to the high cost and poor safety of lithium batteries, my country urgently needs to promote in-depth research on the next generation of energy storage devices. Zn negative electrode has many advantages, including abundant reserves, high safety, low cost and high theoretical capacity (820mAh g -1 ) and low redox potential, aqueous zinc-ion batteries (ZIBs) have great potential as promising energy storage devices. Various electrode materials for rechargeable aqueous zinc-ion batteries have been studied, including metal oxides (manganese oxide, vanadate compounds, etc.), Prussian blue, organic materials, etc. Nevertheless, the large-scale application of rechargeable aqueous zinc-ion batteries (ZIBs) must face the main challenges associated with the zinc anode, which originate from uncontrolled dendrite growth and harmful side reactions, including hydrogen evolution reaction (HER) and byproducts on the surface of the anode. In particular, random dendrite formation can pierce the separator and trigger an internal short circuit of the battery, ultimately leading to low Coulombic efficiency, poor reversibility, and fast capacity decay. The solution to these problems is of great significance for the design of stable aqueous zinc-ion batteries. Researchers have developed many improvement strategies to improve the electrochemical performance of the battery, such as zinc surface modification, preparation of coating protective layers, etc. In the past, the preparation of coating materials mostly adopted organic polymerization, chemical synthesis, thermal synthesis and other methods, which all have different problems, such as the polymerization product is a mixture, chemical synthesis produces impurities, etc. Compared with other methods of preparing coatings, thermal synthesis has the characteristics of high safety, low cost, simple process, and scalable production, which has attracted the interest of many researchers. In the past, some researchers used the Langmuir-Blodgett immersion method to make the coating material adhere to the bare zinc surface. This method has many defects, such as uneven adhesion, weak adhesion, high difficulty in operation, difficulty in controlling variables, and easy contamination of materials. Summary of the invention

[0003] In order to overcome the deficiencies of the prior art, the present invention provides a preparation method and application of a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material to address the problems of zinc dendrite growth, zinc negative electrode surface corrosion, and uneven surface deposition. The present invention also uses the nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material as an aqueous zinc ion battery negative electrode interface coating to prepare an aqueous zinc ion battery negative electrode material. The aqueous zinc ion battery negative electrode coating material uses a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material coated on the surface of a metal zinc foil. The prepared electrode material contains abundant oxygen vacancies, providing active sites for zinc deposition, so that zinc ions can be deposited more evenly on the surface of the negative electrode material, thereby inhibiting the growth of zinc dendrites. The nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material has a higher hydrogen adsorption Gibbs free energy (ΔG H ), which can effectively control the free hydrogen ions in the electrolyte, which is beneficial to inhibit the hydrogen evolution reaction; the raw materials for preparing the interface coating are easy to obtain and the operation is simple, and it can induce uniform zinc deposition, inhibit the growth of zinc dendrites and inhibit the hydrogen evolution reaction of the electrolyte, thereby improving the service life of the aqueous zinc ion battery.

[0004] The above object of the present invention is achieved through the following technical solutions:

[0005] A method for preparing a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material comprises the following steps:

[0006] (1) Grind urea into powder by ball milling twice.

[0007] (2) The powder is placed in a tube furnace for heat treatment to obtain a yellow solid powder.

[0008] (3) adding anhydrous citric acid to ethylene glycol and stirring to obtain solution A;

[0009] (4) adding bismuth nitrate pentahydrate and ferric nitrate nonahydrate to solution A, and stirring to obtain solution B;

[0010] (5) Solution B was dried in a drying oven until it became a dry gel, and then ground into a brown solid powder;

[0011] (6) placing the brown solid powder in a muffle furnace for heat treatment to obtain a reddish brown solid powder;

[0012] (7) The yellow solid powder and the reddish brown solid powder were mixed in a mass ratio of 5:2, ball milled twice to mix evenly, and then placed in a muffle furnace for heat treatment to obtain a pink solid powder;

[0013] (8) The pink solid powder was mixed with polyvinylidene fluoride (PVDF) in a mass ratio of 7:1, and 25-26 drops of N-methylpyrrolidone (NMP) were added and stirred to prepare an aqueous zinc ion battery negative electrode coating material.

[0014] Furthermore, in step (1), the ball milling conditions are: ball milling with a rotation speed of 100-150 r / min and ball milling time of 1 h.

[0015] Furthermore, in step (2), the specific sintering conditions of the tube furnace heat treatment are: a heating rate of 2.3° C. / min, a calcination temperature of 550° C., a calcination time of 2 hours, and a nitrogen atmosphere.

[0016] Furthermore, in step (3), the stirring is performed by magnetic stirring, the rotation speed is 630-650r, and the stirring time is 45min.

[0017] Furthermore, in step (4), the stirring is performed by magnetic stirring, the rotation speed is 630-650r, the stirring time is 6-7h, and the heating temperature is 80°C.

[0018] Furthermore, in step (5), the drying oven temperature is set to 105°C.

[0019] Furthermore, in step (6), the specific sintering conditions of the muffle furnace heat treatment are: a heating rate of 2.3°C / min, a calcination temperature of 550°C, and a calcination time of 4 hours.

[0020] Furthermore, in step (7), the ball mill conditions are: rotation speed of 200-250 r / min; ball milling time of 30 min; and specific sintering conditions of muffle furnace heat treatment are: heating rate of 2.5°C / min, calcination temperature of 300°C, and calcination time of 4 hours.

[0021] The present invention also requests protection for the application of the nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material prepared by the above preparation method in the preparation of aqueous zinc ion battery negative electrode, specifically using a coating machine to evenly coat the prepared coating material on a metal zinc foil.

[0022] A simple method for preparing nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material (NC / BFO) and a simple coating method are provided, and a layer of artificial interface coating is coated on zinc foil to modify the interface properties of the zinc negative electrode. The prepared electrode material is used as an aqueous zinc ion battery to significantly improve the battery specific capacity and charge and discharge cycle stability.

[0023] The present invention first prepares a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material by a simple thermal synthesis method, and uses the material as a zinc negative electrode artificial interface coating material to modify the negative electrode interface. The nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material prepared by the present invention is used as a zinc negative electrode artificial interface coating, provides abundant zinc deposition active sites, promotes uniform deposition of zinc ions, can effectively absorb free hydrogen ions in the electrolyte, and inhibits hydrogen evolution reaction. The interface impedance between the obtained electrode material and the electrolyte is reduced, and the cycle stability of the assembled battery is improved.

[0024] The beneficial effects of the present invention compared with the prior art are:

[0025] (1) The present invention provides a method for preparing a negative electrode coating material for an aqueous zinc ion battery. The nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material contains abundant oxygen vacancies and nitrogen sites, providing active sites for depositing zinc, so that zinc ions can be deposited relatively evenly on the surface of the negative electrode material, thereby inhibiting the growth of zinc dendrites and improving the stability of the aqueous zinc ion battery. The electrode material prepared by the nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material can stably cycle 414 times in an aqueous zinc ion half-cell test, showing excellent stability.

[0026] (2) The present invention provides a method for preparing a negative electrode coating material for an aqueous zinc ion battery, using a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material as the negative electrode coating. The material has strong mechanical properties and excellent chemical stability, does not dissolve in the electrolyte, and does not react chemically with the electrolyte. It can isolate the surface of the metal zinc foil from direct contact with the electrolyte, thereby inhibiting the corrosion of the electrolyte on the zinc surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 100 times (such as Figure 1 a) and 500 times (such as Figure 1 b) Surface morphology of NC / BFO@Zn prepared in Example 1 of the present invention under an optical microscope.

[0028] Figure 2 The contact angle of NC / BFO@Zn prepared in Example 1 ( Figure 2 a) The contact angle of Bare Zn prepared in Comparative Example 1 (e.g. Figure 2 b) Comparison chart.

[0029] Figure 3 This is a comparison chart of half-cell efficiency-cycle number of NC / BFO@Zn prepared in Example 1 and Bare Zn prepared in Comparative Example 1.

[0030] Figure 4 This is a comparison chart of the symmetrical battery impedance of NC / BFO@Zn prepared in Example 1 and Bare Zn prepared in Comparative Example 1.

[0031] Figure 5 This is a comparison chart of half-cell efficiency-cycle number of NC / BFO@Zn prepared in Example 1, BFO@Zn prepared in Comparative Example 2, and Bare Zn prepared in Comparative Example 1.

[0032] Figure 6This is a comparison chart of half-cell efficiency-cycle number of NC / BFO@Zn prepared in Example 1, NC / BFO@Zn-2 prepared in Comparative Example 3, and Bare Zn prepared in Comparative Example 1.

[0033] Figure 7 This is a comparison chart of half-cell efficiency-cycle number of NC / BFO@Zn prepared in Example 1, NC / BFO@Zn-3 prepared in Comparative Example 4, and Bare Zn prepared in Comparative Example 1. DETAILED DESCRIPTION

[0034] The present invention is described in detail below by specific examples, but the protection scope of the present invention is not limited. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels.

[0035] The present invention provides a method for preparing a negative electrode coating material for an aqueous zinc ion battery. A nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material (NC / BFO) is prepared, and the negative electrode material for an aqueous zinc ion battery is prepared using the material. The negative electrode coating material for an aqueous zinc ion battery is coated on the surface of a metal zinc foil with nitrogen-doped graphite carbon-coated bismuth zinc ferrite (NC / BFO), which can provide abundant active sites, so that zinc ions can be deposited more evenly and the growth of zinc dendrites can be inhibited; and the material has excellent mechanical strength and chemical stability, which effectively inhibits the corrosion of the electrolyte to the negative electrode; the impedance of the symmetrical battery assembled with the material is significantly reduced compared to pure zinc, and the half-cell cycle efficiency stability is significantly improved, thereby improving the service life of the aqueous zinc ion battery.

[0036] Example 1

[0037] A method for preparing a negative electrode coating material for an aqueous zinc ion battery,

[0038] (1) Grind urea into fine powder and ball-mill it twice to obtain mixed powder A;

[0039] (2) The mixed powder A was placed in a covered crucible and heated to 550°C in a tube furnace at a heating rate of 2.3°C / min for 4 hours. The mixture was calcined for 2 hours in an argon atmosphere and then cooled to room temperature to obtain a yellow solid powder named NC.

[0040] (3) Add 0.042 mol of anhydrous citric acid to 20 mL of ethylene glycol and stir for 45 min to obtain solution A;

[0041] (4) adding 0.0055 mol of bismuth nitrate pentahydrate and 0.005 mol of ferric nitrate nonahydrate to solution A and stirring for 6-7 hours to obtain solution B;

[0042] (5) Solution B was dried in a drying oven at 105°C until it became a dry gel, and then ground into powder B;

[0043] (6) Powder B was placed in a ceramic crucible and calcined at 550 °C in a muffle furnace for 4 h at a heating rate of 2.3 °C / min. The powder obtained was ground into powder and named BFO.

[0044] (7) BFO and NC were mixed in a mass ratio of 2:5 and mechanically ground for 30 min to obtain powder C, which was then transferred to a muffle furnace and heated to 300 °C at a heating rate of 2.5 °C / min for 2 h, calcined for 4 h, and then cooled to room temperature to obtain a solid powder named NC / BFO;

[0045] (8) Solid powder NC / BFO and polyvinylidene fluoride (PVDF) were mixed in a ratio of 7:1, and 25-26 drops of N-methylpyrrolidone (NMP) were added and stirred to prepare a mixed coating material.

[0046] (9) Using a coating machine, the prepared coating material is evenly coated on a metal zinc foil to obtain a negative electrode material. The negative electrode material is named NC / BFO@Zn.

[0047] Comparative Example 1

[0048] The metal zinc foil was not treated in any way and was named Bare Zn.

[0049] Comparative Example 2

[0050] (1) Add 0.042 mol of anhydrous citric acid to 20 mL of ethylene glycol and stir for 45 min to obtain solution A;

[0051] (2) adding 0.0055 mol of bismuth nitrate pentahydrate and 0.005 mol of ferric nitrate nonahydrate to solution A and stirring for 6-7 hours to obtain solution B;

[0052] (3) Solution B was dried in a drying oven at 105°C until it became a dry gel, and then ground into powder B;

[0053] (4) Powder B was placed in a ceramic crucible and calcined at 550 °C in a muffle furnace for 4 h at a heating rate of 2.3 °C / min. The solid powder obtained was ground into powder and named BFO.

[0054] (5) Solid powder BFO and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 5:1, and 25-26 drops of N-methylpyrrolidone (NMP) are added and stirred to prepare a mixed coating material.

[0055] (4) Using a coating machine, the prepared mixed coating material is evenly coated on a metal zinc foil to obtain a negative electrode material. The negative electrode material is named BFO@Zn.

[0056] Comparative Example 3

[0057] (1) Grind urea into fine powder and ball-mill it twice to obtain mixed powder A;

[0058] (2) The mixed powder A was placed in a covered crucible and heated to 550°C in a muffle furnace at a heating rate of 2.3°C / min for 4 hours, calcined for 2 hours, and then cooled to room temperature to obtain a yellow solid powder named NC.

[0059] (3) Add 0.042 mol of anhydrous citric acid to 20 mL of ethylene glycol and stir for 45 min to obtain solution A;

[0060] (4) adding 0.0055 mol of bismuth nitrate pentahydrate and 0.005 mol of ferric nitrate nonahydrate to solution A and stirring for 6-7 hours to obtain solution B;

[0061] (5) Solution B was dried in a drying oven at 105°C until it became a dry gel, and then ground into powder B;

[0062] (6) Powder B was placed in a ceramic crucible and calcined at 550 °C in a muffle furnace for 4 h at a heating rate of 2.3 °C / min. The powder obtained was ground into powder and named BFO.

[0063] (7) BFO and NC were mixed in a mass ratio of 1:10 and mechanically ground for 30 min to obtain powder C, which was then transferred to a muffle furnace and heated to 300 °C at a heating rate of 2.5 °C / min for 2 h, calcined for 4 h, and then cooled to room temperature to obtain a solid powder named NC / BFO-2;

[0064] (8) Solid powder NC / BFO-2 and polyvinylidene fluoride (PVDF) were mixed in a ratio of 11:1, and 25-26 drops of N-methylpyrrolidone (NMP) were added and stirred to prepare a mixed coating material.

[0065] (9) Using a coating machine, the prepared mixed coating material is evenly coated on a metal zinc foil to obtain a negative electrode material. The negative electrode material is named NC / BFO@Zn-2.

[0066] Comparative Example 4

[0067] (1) Grind urea into fine powder and ball-mill it twice to obtain mixed powder A;

[0068] (2) The mixed powder A was placed in a covered crucible and heated to 550°C in a muffle furnace at a heating rate of 2.3°C / min for 4 hours, calcined for 2 hours, and then cooled to room temperature to obtain a yellow solid powder named NC.

[0069] (3) Add 0.042 mol of anhydrous citric acid to 20 mL of ethylene glycol and stir for 45 min to obtain solution A;

[0070] (4) adding 0.0055 mol of bismuth nitrate pentahydrate and 0.005 mol of ferric nitrate nonahydrate to solution A and stirring for 6-7 hours to obtain solution B;

[0071] (5) Solution B was dried in a drying oven at 105°C until it became a dry gel, and then ground into powder B;

[0072] (6) Powder B was placed in a ceramic crucible and calcined at 550 °C in a muffle furnace for 4 h at a heating rate of 2.3 °C / min. The powder obtained was ground into powder and named BFO.

[0073] (7) BFO and NC were mixed in a mass ratio of 1:5 and mechanically ground for 30 min to obtain powder C, which was then transferred to a muffle furnace and heated to 300 °C at a heating rate of 2.5 °C / min for 2 h, calcined for 4 h, and then cooled to room temperature to obtain a solid powder named NC / BFO-3;

[0074] (8) Solid powder NC / BFO-3 and polyvinylidene fluoride (PVDF) were mixed in a ratio of 6:1, and 25-26 drops of N-methylpyrrolidone (NMP) were added and stirred to prepare a mixed coating material.

[0075] (9) Using a coating machine, the prepared mixed coating material is evenly coated on a metal zinc foil to obtain a negative electrode material. The negative electrode material is named NC / BFO@Zn-3.

[0076] Application Example 1

[0077] The NC / BFO@Zn prepared in Example 1 was assembled into an aqueous zinc ion half-cell, wherein the positive electrode material was copper foil, the negative electrode material was NC / BFO@Zn prepared in Example 1, and the electrolyte was 2 mol L -1 Various electrochemical tests were performed on zinc sulfate solution. Test conditions: at a current density of 5 mA cm -2 , capacity cutoff 1mAh cm -2 Half-cell test was performed under the condition.

[0078] The NC / BFO@Zn prepared in Example 1 was assembled into an aqueous zinc ion symmetric battery, wherein the positive electrode material was the NC / BFO@Zn prepared in Example 1, the negative electrode material was the NC / BFO@Zn prepared in Example 1, and the electrolyte was 2 mol L -1 Zinc sulfate solutions were used for various electrochemical tests.

[0079] Test results: attached Figure 2 It can be seen that the contact angle between the NC / BFO@Zn prepared in Example 1 and the electrolyte is 133.70°, which is much larger than that of the Bare Zn prepared in Comparative Example 1, showing excellent hydrophobicity. Figure 3The NC / BFO@Zn assembled half-cell prepared in Example 1 was charged at a current density of 5 mA cm -2 , capacity cutoff 1mAh cm -2 Under the test, it stably cycled 414 times, showing excellent zinc plating / stripping recoverability. Compared with the Bare Zn prepared in comparative example 1, which could only stably cycle 40 times, it showed excellent stability. The coating material has significantly better stability for aqueous zinc ion batteries than the prior art.

[0080] The NC / BFO@Zn prepared in Example 1 and the Bare Zn prepared in Comparative Example 1 were assembled into symmetrical batteries and impedance tests were performed. Figure 4 It can be seen that the impedance value of NC / BFO@Zn prepared in Example 1 is 90Ω, which is much smaller than the impedance value of Bare Zn prepared in Comparative Example 1.

[0081] Application Comparative Example 1

[0082] The bare Zn prepared in comparative example 1 was assembled into a half-cell for testing, wherein the positive electrode material was copper foil, the negative electrode material was bare Zn prepared in comparative example 1, and the electrolyte was 2 mol L -1 Various electrochemical tests were performed on zinc sulfate solution at a current density of 5 mA cm -2 , capacity cutoff 1mAh cm -2 .

[0083] The Bare Zn prepared in Comparative Example 1 was assembled into an aqueous zinc ion symmetric battery, wherein the positive electrode material was the Bare Zn prepared in Comparative Example 1, the negative electrode material was the Bare Zn prepared in Comparative Example 1, and the electrolyte was 2 mol L -1 Zinc sulfate solutions were used for various electrochemical tests.

[0084] Test results: attached Figure 3 It can be seen that the bare Zn assembled half-cell prepared in Comparative Example 1 can only stably cycle 40 cycles, and after 40 cycles, the CE fluctuates greatly and short circuits occur. Figure 4 It can be seen that the impedance value of the symmetrical battery assembled with Bare Zn prepared in Comparative Example 1 is 890Ω.

[0085] Application Comparative Example 2

[0086] The BFO@Zn prepared in Comparative Example 2 was assembled into a half-cell for testing, wherein the positive electrode material was copper foil, the negative electrode material was BFO@Zn prepared in Comparative Example 2, and the electrolyte was 2 mol L -1 Various electrochemical tests were performed on zinc sulfate solution at a current density of 5 mA cm -2 , capacity cutoff 1mAh cm -2 .

[0087] Test results: attached Figure 5 It can be seen that the half-cell assembled with BFO@Zn prepared in Comparative Example 2 can only be stably cycled for 160 cycles, and a short circuit occurs after 160 cycles.

[0088] Application Comparative Example 3

[0089] The NC / BFO@Zn-2 prepared in Comparative Example 3 was assembled into a half-cell for testing, wherein the positive electrode material was copper foil, the negative electrode material was NC / BFO@Zn-2 prepared in Comparative Example 3, and the electrolyte was 2 mol L -1 Various electrochemical tests were performed on zinc sulfate solution at a current density of 5 mA cm -2 , capacity cutoff 1mAh cm -2 .

[0090] Test results: attached Figure 6 It can be seen that the half-cell assembled with NC / BFO@Zn-2 prepared in Comparative Example 3 can only be cycled 139 times, and its stability is much lower than that of the half-cell assembled with NC / BFO@Zn prepared in Example 1.

[0091] Application Comparative Example 4

[0092] The NC / BFO@Zn-3 prepared in Comparative Example 4 was assembled into a half-cell for testing, wherein the positive electrode material was copper foil, the negative electrode material was NC / BFO@Zn-3 prepared in Comparative Example 4, and the electrolyte was 2 mol L -1 Various electrochemical tests were performed on zinc sulfate solution at a current density of 5 mA cm -2 , capacity cutoff 1mAh cm -2 .

[0093] Test results: Test results: Attached Figure 6 It can be seen that the half-cell assembled with NC / BFO@Zn-3 prepared in Comparative Example 4 can only be cycled 370 times, and its stability is lower than that of the half-cell assembled with NC / BFO@Zn prepared in Example 1.

[0094] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material, characterized in that: The following steps are involved: (1) Grind urea into powder by ball milling twice. (2) The powder is placed in a tube furnace for heat treatment to obtain a yellow solid powder. (3) adding anhydrous citric acid to ethylene glycol and stirring to obtain solution A; (4) adding bismuth nitrate pentahydrate and ferric nitrate nonahydrate to solution A, and stirring to obtain solution B; (5) Solution B was dried in a drying oven until it became a dry gel, and then ground into a brown solid powder; (6) placing the brown solid powder in a muffle furnace for heat treatment to obtain a reddish brown solid powder; (7) The yellow solid powder and the reddish brown solid powder were mixed in a mass ratio of 5:2, ball milled twice to mix evenly, and then heat treated in a muffle furnace to obtain a pink solid powder; (8) The pink solid powder was mixed with polyvinylidene fluoride (PVDF) in a mass ratio of 7:1, and 25-26 drops of N-methylpyrrolidone (NMP) were added and stirred to prepare an aqueous zinc ion battery negative electrode coating material.

2. The method for preparing a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material according to claim 1, characterized in that: In step (1), the ball milling conditions are: ball milling with a rotation speed of 100-150 r / min and ball milling time of 1 h.

3. The method for preparing a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material according to claim 1, characterized in that: In step (2), the specific sintering conditions of the tube furnace heat treatment are: a heating rate of 2.3°C / min, a calcination temperature of 550°C, a calcination time of 2 hours, and a nitrogen atmosphere.

4. The method for preparing a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material according to claim 1, characterized in that: In step (3), magnetic stirring is used for stirring, the rotation speed is 630-650r, and the stirring time is 45min.

5. The method for preparing a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material according to claim 1, characterized in that: In step (4), magnetic stirring is used for stirring, the rotation speed is 630-650r, the stirring time is 6-7h, and the heating temperature is 80°C.

6. The method for preparing a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material according to claim 1, characterized in that: In step (5), the drying oven temperature is set to 105°C.

7. The method for preparing a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material according to claim 1, characterized in that: In step (6), the specific sintering conditions of the muffle furnace heat treatment are: a heating rate of 2.3°C / min, a calcination temperature of 550°C, and a calcination time of 4 hours.

8. The method for preparing a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material according to claim 1, characterized in that: In step (7), the ball mill conditions are: rotation speed of 200-250 r / min; ball milling time of 30 min.

9. The method for preparing a nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material according to claim 1, characterized in that: The specific sintering conditions of the muffle furnace heat treatment are: heating rate of 2.5°C / min, calcination temperature of 300°C, and calcination time of 4 hours.

10. Use of the nitrogen-doped graphite carbon-coated bismuth zinc ferrite negative electrode coating material according to any one of claims 1 to 9 in preparing a negative electrode for an aqueous zinc ion battery.

Citation Information

Patent Citations

  • Bismuth vanadium / nickel hydroxide secondary alkaline battery and preparation method thereof

    CN106450508A

  • Bismuth ferrite / nickel hydroxide secondary alkali battery and preparation method therefor

    CN106654401A

  • MOF-based NiO-coated BiFeO3 / C composite material as well as preparation method and application thereof

    CN115275130A

  • Graphene oxide coated bismuth ferrite anode material, preparation method thereof and negative plate

    CN118929770A

  • Preparation method of heteroatom-doped barium titanate and application of heteroatom-doped barium titanate in zinc negative electrode

    CN119029173A